Urgensi Pemasaran Digital bagi Pelaku UMKM di Wilayah Kabupaten Sleman Provinsi DIY - Risdwiyanto, Andriya; Wijono, Djoko; Kusumawati, Diana Anggraini; Hertini, Etty Sri; Nurani, Putri Ana (Jurnal Masyarakat Indonesia (Jumas), 2025)
This community service is carried out for MSME actors in Sleman Regency in the Province of DIY. The theme of this community service is the urgency of digital marketing for MSME actors in the Sleman Regency area of ​​the Province of DIY. MSMEs as a crucial business and making a major contribution to job creation, require knowledge and digital marketing skills that still need to be improved. So that in the future MSME actors in Sleman Regency will be able to improve their abilities or add skills to take full advantage of digital marketing. The service method is carried out in two ways, namely the lecture method and training. The results of this service activity are expected to improve the abilities or skills of MSME actors in Sleman Regency with the hope that after the service activity they will be able to improve their abilities or add skills to take full advantage of the urgency of digital marketing.